(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2022)
Phraseology (Greek phrasis - “expression”, logos - “teaching”) is a section of linguistics that studies stable combinations in a language. Phraseology is also called a set of stable combinations in the language as a whole, in the language of a particular writer, in the language of a particular work of art, etc.